EBB among the Nightingales: Elizabeth Barrett Browning, Felicia Hemans, and Generative Rivalry in the Poetess Tradition. Issue 2 (3rd April 2019) - Taylor, Beverly
ABSTRACT: Shortly before Elizabeth Barrett Browning turned 15, she declared, "I am not content till I excel". Competition with the poetess tradition proved to be an especially generative form of collaboration. Her critique of poetess verse is evident in forsaken woman poems such as "Bianca among the Nightingales" and "Bertha in the Lane". The generative energy of EBB's competitiveness with poetesses manifests itself especially in her poems that engage with works by Felicia Hemans, pairings in which EBB used specific settings and situations from Hemans's works to recast the earlier poet's themes and tones, eschewing poetess conventions and often producing more complex woman-centered poems. This essay explores relationships between EBB's "The Romaunt of the Page" and Hemans's "Woman on the Field of Battle", and between EBB's "The Runaway Slave at Pilgrim's Point and Hemans's "The Landing of the Pilgrim Fathers in New England" to suggest EBB's productive engagement with the poetess tradition.